Discipline and puppies: the powers of pet keeping. Issue 3 (25th February 2020) - Redmalm, David
Abstract : Purpose: This article adopts Foucault's notion of a bipolar technology of disciplinary power and regulatory biopower to address the tension between discipline and freedom in domestic relationships between human and nonhuman animals commonly referred to as "pets." In doing so, the article examines the promises and pitfalls of thinking through pet keeping as a form of lived, posthumanist critique. Design/methodology/approach: The argument relies on an interview study with 20 pet owners—most of the interviews conducted in their homes together with their pets—to conceptualize how they organize their lives in relation to their pets. Findings: The analysis shows that the boundaries of the home, the play of power between bodies, and the "conditions of an unconditional love" are central to producing the pet relationship as inherently meaningful and as an indispensable part of the lives of both pet keepers and pets. A balance between discipline and freedom enables the construction of both human and other identities: pet owners produce their pets' subjectivity by speaking of them as autonomous persons, while pets' presence in the home also enables their owners' subjectivity. Social implications: The article critically examines interspecies relationships, which by extension can benefit nonhuman animals. It argues that pet keeping can challenge anthropocentrism and unsustainable consumption lifestyles, but it may also reinforce prevailing biopolitical logics, if it remains maintained within a secluded domestic or cultural sphere. Originality/value: The article draws on original data. While Foucauldian theory has been used to discuss pet keeping, empirical studies of pet keeping that rely on this theoretical framework are scarce.